The Costs of Colonoscopy in a Canadian Hospital using a Microcosting Approach. (2008) - Sharara, Nour; Adam, Viviane; Crott, Ralph; Barkun, Alan N
Abstract : BACKGROUND: Colonoscopy has become accepted as one of the most effective methods of screening patients for colorectal cancer, and is used to remove the majority of colonic adenomas. OBJECTIVE: Because of the paucity of such estimates in the literature and the significant number of candidates for this procedure, the present study was performed to estimate the direct hospital costs of both diagnostic and therapeutic (polypectomy) colonoscopy. METHODS: A microcosting methodology was used to itemize the costs of colonoscopy. Variable and fixed costs were divided into labour, supplies, equipment and overhead costs. A third-party payer perspective was adopted. All costs are expressed in 2007 Canadian dollars. RESULTS: The cost of a diagnostic colonoscopy was $157 and the cost of a therapeutic colonoscopy was $199. Overhead costs represented approximately 30% of these amounts. When physician fees were added, these costs rose to $352 and $467, respectively. CONCLUSION: Because the overhead costs represent a large proportion of the total costs, allocation methods for these costs should be improved to allow for a more precise determination of the total costs of a colonoscopy. These estimates are useful when analyzing the cost-effectiveness of a strategy that uses colonoscopy when screening for colorectal cancer.